Guidelines for Fluorescent Guided Biallelic HDR Targeting Selection With PiggyBac System Removal for Gene Editing - Jarazo, Javier; Qing, Xiaobing; Schwamborn, Jens C. (Frontiers in Genetics, 2019)
The development of new and easy-to-use nucleases, such as CRISPR/Cas9, made tools for gene editing widely accessible to the scientific community. Cas9-based gene editing protocols are robust for creating knock-out models, the generation of single nucleotide transitions or transversions remains challenging. This is mainly due to the low frequency of homology directed repair, in consequence it is required the screening a high number of clones to identify positive events Moreover, lack of simultaneous biallelic modifications, frequently results in second-allele indels. For example, while one allele might undergo homology directed repair, the second can undergo non-homologous end joining repair. Here we present a step-wise protocol for biallelic gene editing. It uses a combination of donors carrying combination of fluorescent reporters alongside homology arms directed to the same genomic region for biallelic targeting. These homology arms carry the desired composite of modifications to be introduced (homozygous or heterozygous changes). Plus, the backbone of the plasmid carries a third fluorescent reporter for negative selection (to discard random integration events). Fluorescent selection of non-random biallelic targeted clones can be performed by microscopy guided picking or cell sorting (FACS). The positive selection module (PSM), carrying the fluorescence reporter and an antibiotic resistance, is flanked by inverted terminal repeats (ITR) that are recognized by transposase. Upon purification of the clones correctly modified, transfection of the excision-only transposase allows removing the PSM resulting in the integration of the desired modifications only.